Field Engineers' Scheduling at Oil Rigs: a Case Study - Ateekh-Ur-Rehman, .; Usmani, Y. S. (Engineering, Technology & Applied Science Research, 2012)
Oil exploration and production operations face a number of challenges. Professional planners have to design solutions for various practical problems or issues. However, the time consumed is often very extensive because of the large number of possible solutions. Further, the matter of choosing the best solution remains. The present paper investigates a problem related to leading companies in the energy and chemical manufacturing sector of the oil and gas industry. Each company’s field engineers are expensive and valuable assets. Therefore, an optimized roster is rather important. In the present paper, the objective is to design a field engineers’ schedule which would be both feasible and satisfying towards the various demands of rigs, with minimum operational cost to the company. An efficient and quick optimization technique is presented to schedule the shifts of field engineers.